2020
DOI: 10.1007/s00394-020-02247-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine wine or sour grapes? A systematic review and meta-analysis of the impact of red wine polyphenols on vascular health

Abstract: Purpose Red wine polyphenols (RWP) are plant-based molecules that have been extensively studied in relation to their protective effects on vascular health in both animals and humans. The aim of this review was to quantify and compare the efficacy of RWP and pure resveratrol on outcomes measures of vascular health and function in both animals and humans. Methods Comprehensive database searches were carried out through PubMed, Web of Science and OVID for randomised, placebo-controlled studies in both animals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 152 publications
(213 reference statements)
2
34
0
Order By: Relevance
“…No significant effects were found for DBP (−1.0 mmHg, 95% CI −2.2 to 0.3; p = 0.139). The authors suggested that the non-significant effect on DBP could be attributed to the small changes seen in DBP in clinical hypertension [109]. Nonetheless, these findings are consistent with previous studies on resveratrol [95].…”
Section: Hypertensionsupporting
confidence: 81%
“…No significant effects were found for DBP (−1.0 mmHg, 95% CI −2.2 to 0.3; p = 0.139). The authors suggested that the non-significant effect on DBP could be attributed to the small changes seen in DBP in clinical hypertension [109]. Nonetheless, these findings are consistent with previous studies on resveratrol [95].…”
Section: Hypertensionsupporting
confidence: 81%
“…In these studies, the hypothesis was tested that post-oral delivery of non-caloric tastants will result in a net decreased energy intake compared with placebo. Klaassen et al recently published a systematic review and meta-analysis on this topic [ 63 ]. These authors report on the effects of gastrointestinal administration of tastants on eating behavior.…”
Section: Topics In Intestinal Brake Appetite and Energy Intakementioning
confidence: 99%
“…Finally, animal studies often employ very high doses of grape (poly)phenols, e.g., resveratrol and their results cannot be readily transferred to humans, who would need to ingest several grams of extracts to replicate the same effects. Indeed, a discrepancy between animal and human effects has just been underscored [ 5 ] and resveratrol’s potential toxicity has been recently reviewed [ 67 ]. An often overlooked paper reported that resveratrol promoted atherosclerotic development in hypercholesterolemic rabbits, by a mechanism that is independent of observed differences in gross animal health, liver function, plasma cholesterol concentrations, or LDL oxidative status [ 68 ].…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…The debate on alcohol use and health is becoming heavily polarized: one party underscores a large amount of data in support of the J curve [ 1 , 3 ] whereas the other side dismisses such evidence and calls for total abstention [ 2 , 3 ]. In support of the former, researchers and the lay press often advocate the health benefits of (poly)phenol consumption via red wine intake and cite the vast amount of in vitro literature that would corroborate the hypothesis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%